Vulnerable to mental health problems: Pregnant women and husband's perception in Surakarta, Indonesia; Vulnerabilidad a los problemas de salud mental: Percepción de las mujeres embarazadas y de sus maridos en Surakarta, Indonesia - Kusumawati, Yuli (Elsevier Doyma, 2022)
Objective: This study aims to explore the perception of women and their husbands on the vulnerability of pregnant women to mental health disorders. Method: Qualitative study using a phenomenological approach. The inclusion criteria were pregnant women of the second and third-trimester gestation (13–35 weeks). The exclusion criteria were pregnant women with complications and who had a family record of mental disorders. Data was collected using focus group discussion and in-depth interviews at four Primary Health Cares in Surakarta, Indonesia. Then, the data were analyzed through thematic analysis, which was supported by the OpenCode 4.02® software. Results: This study uncovered two main topics, firstly the factors that trigger the vulnerability of pregnant women to experience mental disorders and secondly perceived barriers to managing mental health during pregnancy and postpartum. Pregnant women and husbands recognize that they need to get mental health information. Conclusion: Unstable emotions during pregnancy are considered normal and neglected by their surroundings. Lack of knowledge about mental health in pregnancy justifies the need to increase education in this area in order to prevent prenatal and postpartum depression. © 2022 Elsevier España, S.L.U.